Reservoir Perencanaan Struktur Reservoir Air Bersih Desa Pecangaan Kulon, Kecamatan Pecangaan, Kabupaten Jepara: Perencanaan Struktur Reservoir Air Bersih Desa Pecangaan Kulon, Kecamatan Pecangaan, Kabupaten Jepara - Prasetya, Herry Puguh; Umam, Khotibul; Rochmanto, Decky (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2021)
The existence of clean water in a village is very important, considering the activities of rural life which are now starting to be dynamic. This planning is based on SNI 7509:2011 concerning Procedures for Technical Planning for Distribution Networks and Service Units for the Clean Water Supply System and the Regulation of the Minister of Public Works Number 18/PRT/M/2007 concerning Implementation of Drinking Water Supply System Development. The reservoir is planned to use reinforced concrete material with a base plate thickness of 250 mm and reinforcement D13-150, a concrete wall thickness of 150 mm and reinforcement D13-100, and a cover plate with a thickness of 100 mm with reinforcement 10 - 150. Beam dimensions are 20 x 30 cm with reinforcement 5D13 support and stirrup reinforcement 8-150 and field reinforcement 4D13 and stirrup reinforcement 8-200. Column dimensions are 25 x 25 cm with 6D13 main reinforcement and 8-150 stirrup reinforcement.